DIMENSI PASTORAL DALAM DOA: MENEMUKENALI PRAKTIK DOA YANG BERTANGGUNGJAWAB DALAM PELAYANAN PENDAMPINGAN DAN KONSELING PASTORAL - Besly J.T Messakh (Sekolah Tinggi Theologia Abdiel, 2019)
Looking from a pastoral care and counseling perspective, prayer as a ritual is a human response for God’s action. As a response, prayer presupposes a responsible communication with God as absolute authority in one’s life. If the communication running well, the pastoral function of prayer as a ritual enhance people well-being mentality and spirituality. Therefore, when doing pastoral care or pastoral counseling, pastoral caregiver needs to make sure that people have healthy communication with true God as the Ultimate Absolute Authority. For those reasons, a pastoral caregiver should understand about the theological principle in praying and have ability to use prayer as pastoral means for themselves and people who need their pastoral ministry.